PENGARUH INSENTIF, KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA GURU MADRASAH DINIYAH TAKLIMIYAH AWALIYAH DI KOTA BUKITTINGGI - Naldi, Syukri; Tasri, Evi Susanti; Heliyani, Heliyani (Jurnal Ilmiah Ilmu Manajemen, 2020)
This type of research is an explanatory research with a quantitative approach. The target population in this study was MDTA teachers in Bukittinggi City, totaling 217 people, a sample of 69 respondents. The sampling technique used in this study is proportional random sampling. Data collection methods used are by distributing questionnaires. The data analysis technique used in this study is quantitative analysis using path analysis. This study aims to use an analysis of how much influence the incentives, Competencies and Work Disciplines have on the performance of MDTA Teachers in Bukittinggi City. The results of the data analysis state that, the provision of Incentives, Competence and Work Discipline has an effect on improving teacher performance by 79.8%, the remaining 20.2% is explained by other variables not examined.